Experimental investigations of thermal performance improvement of aluminum ceiling panel for heating and cooling by covering its surface with paint - Amanowicz Łukasz; Wojtkowiak Janusz (E3S Web of Conferences, 2018)
Due to the low emissivity of raw metal surface (i.e. aluminum), the specific heating or cooling performance of non-painted surfaces is powered mainly on the natural convection and is relatively small. It can be sufficient for low energy buildings but not for the traditional ones. To increase the heat exchange through the radiation one can cover the raw surface with paint to increase its emissivity. To investigate the influence of paint cover on the heating and cooling performance of the ceiling-oriented flat aluminum surface the experimental investigations were done. The experiment was conducted on the aluminum ceiling panel with heat exchange surface of the dimensions 0.32 ⨯ 3.0 m. Heating performance of painted surface increased from 2.3 to 2.8 times and cooling performance increased from 1.5 to 1.7 times in the comparison to the non-painted one.